2021
DOI: 10.1007/s11920-021-01263-7
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Child Environments and Its Psychological Consequences After the Fukushima Disaster: a Narrative Review Based on the Ecological Systems Model

Abstract: Purpose of Review: A high prevalence of clinically significant mental health problems was found in children affected by the Fukushima disaster in Japan. We reviewed the literature on child mental health to examine how disasters impacted children in Fukushima.Recent Findings: Children's environments, such as family and peer systems, were disrupted by radiation concerns and evacuation. As children struggled with less resources at home and school, they also had to deal with discrimination. Various interventions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These disasters, whether large, medium or small, impact children's safety and education (Gibbs et al, 2019). When education is disrupted, a child's learning can be disrupted, sometimes permanently, which can have lasting negative impacts, both economic and social, on the child, their family, and the community (Mizuki et al, 2021;Peek, 2008).…”
Section: Disaster Safe School Conceptmentioning
confidence: 99%
“…These disasters, whether large, medium or small, impact children's safety and education (Gibbs et al, 2019). When education is disrupted, a child's learning can be disrupted, sometimes permanently, which can have lasting negative impacts, both economic and social, on the child, their family, and the community (Mizuki et al, 2021;Peek, 2008).…”
Section: Disaster Safe School Conceptmentioning
confidence: 99%
“…is modeling technology is introduced into the bill details in WeChat [16]. It can store the daily expenditure and income of users and finally integrate the data as a whole.…”
Section: Related Workmentioning
confidence: 99%
“…Evacuees may nd it challenging if they cannot con de in family members. In many disasters, families evacuate together and continue their post-disaster lives toward recovery (10,11); however, in Fukushima prefecture, especially among the younger generation with children, there have been many cases of family separation, with only grandparents and fathers remaining in Fukushima owing to work, school, and radiation concerns (12,13). Nevertheless, few studies have reported the importance of con ding in family members during disasters in the context of the association with mental health conditions.…”
Section: Introductionmentioning
confidence: 99%